Aphally in the stylommatophoran land snail Phaedusa (Clausiliidae: Phaedusinae) in Timor and its systematic implications. (1st October 2016) - Köhler, Frank; Burg Mayer, Guilherme
ABSTRACT: The Clausiliidae (subfamily Phaedusinae) of the Lesser Sunda island of Timor are poorly studied. To date, one species with a rather confusing taxonomic history, Phaedusa timorensis Nordsieck, 2007, has been recorded from West Timor. Based on the study of recently collected material, we present the first record of clausiliids from Timor-Leste (East Timor). Two species, which live in sympatry with each other, are recognised and described based on comparative shell morphology and mitochondrial differentiation: Phaedusa ramelauensis n. sp. and P. angustocostata n. sp. Both species are ovoviviparous, retaining shelled juveniles in their oviducts. One population of P. ramelauensis consists of individuals that lack male organs while having fully functional female organs. As with similar cases in other stylommatophoran families, the aphally is hypothesised to be a byproduct of either within-species polymorphism or hybridisation and to have no bearing on the taxonomy of these terrestrial snails. Because aphally is the key characteristic of Renschiphaedusa Loosjes and Loosjes-van Bemmel, 1973, this genus-level taxon is placed in the synonymy of Phaedusa H. and A. Adams, 1855 . http://zoobank.org/urn:lsid:zoobank.org:pub:528EB46B-5E4F-49B6-AECE-4DFE20B4B4A0